Nondegenerate germs of holomorphic foliations with prescribed holonomy - Ribón, Javier (2025)
We are interested in characterizing the holonomy maps associated to integral curves of nondegenerate singularities of holomorphic vector fields. Such a description is well-known in dimension 2 where is a key ingredient in the study of reduced singularities. Themost intricate case in the 2 dimensional setting corresponds to (Siegel) saddle singularities. This work treats the analogous problem for saddles in higher dimension. We show that any germ of holomorphic biholomorphism, in any dimension, can be obtained as the holonomy map associated to an integral curve of a saddle singularity. A natural question is whether we can prescribe the linear part of the saddle germ of vector field provided the holonomy map. The answer to this question is known to be positive in dimension 2.We see that this is not the case in higher dimension. In spite of this, we provide a positive result under a natural condition for the holonomy map.